Nitrogen Flow in Diazotrophic Cyanobacterium Aphanizomenon flos-aquae Is Altered by Cyanophage Infection - Kuznecova, Jolita; Šulčius, Sigitas; Vogts, Angela; Voss, Maren; Jürgens, Klaus; Šimoliūnas, Eugenijus (Frontiers in Microbiology, 2020)
The role of viruses for net 15N2 assimilation rate, expression of nitrogenase reductase gene (nifH) and changes in nitrogen enrichment (15N/14N) was studied in the diazotrophic cyanobacterium Aphanizomenon flos-aquae during infection by the cyanophage vB_AphaS-CL131. We found that while the growth of A. flos-aquae was inhibited by cyanophage addition, there were no significant differences in nitrogen fixation rates and nifH expression level between the infected and control A. flos-aquae cultures. This implies that cyanophage genome replication and progeny production within the vegetative cells does not interfere with the N2 fixation reactions in the heterocytes of these cyanobacteria. However, higher 15N enrichment at the rims of heterocytes of the infected A. flos-aquae, revealed by NanoSIMS analysis indicates the accumulation of fixed nitrogen in response to cyanophage addition. This suggest reduced nitrogen transport to vegetative cells and the alterations in the flow of fixed nitrogen within the filaments. In addition, we found that cyanophage lysis resulted in a substantial release of ammonium into culture medium. Cyanophage infection seems to substantially redirect N flow from cyanobacterial biomass to the production of N storage compounds and N release.